DETERMINATION OF HALF AND TENTH VALUE LAYER PRIMARY AND SECONDARY WALLS OF X-RAY ROOM IN BALI JIMBARAN GENERAL HOSPITAL - Widianingsih, Ni Kadek Indah; Sutapa, Gusti Ngurah; Kasmawan, I Gde Antha; Sandi, I Nengah; Baskoro, Winardi Tjahyo; Wendri, Nyoman; Prayuda, I Made Ardi (Universitas Mataram, 2023)
The research has been carried out on the HVL and TVL values ​​of the primary and secondary walls of the radiology installation radiology room at RSU Bali Jimbaran. The aims of this study were (1) to determine HVL and TVL values ​​on the primary and secondary walls in the x-ray room, (2) to determine the differences between HVL and TVL values ​​if the tube voltages are varied. In determining the HVL and TVL values, ​​the linear attenuation coefficient of the walls must be known. The linear attenuation coefficient was determined by measuring the wall thickness by using a caliper, and measuring the radiation dose rate before and after passing through the primary and secondary walls. The results of the analysis of the HVL and TVL values ​​on the primary wall were 1.668 cm and 5.540 cm, meanwhile on the secondary wall ​​were 1.915 cm and 6.362 cm. When the voltage was varied 40 kV, 50 kV, 60 kV and 70 kV, there was no difference in the HVL or TVL values. Based on the results of the analysis, the HVL and TVL values ​​on the primary and secondary walls have a significant average difference.